2018
DOI: 10.1108/bfj-11-2017-0604
|View full text |Cite
|
Sign up to set email alerts
|

Innovating out of the fishmeal trap

Abstract: Purpose-The purpose of this paper is to examine the potential market impacts of the use of insect-based protein for fish feed as an innovative approach out of the fish-meal trap. Design/methodology/approach-An online questionnaire was used to elicit information on fish consumption choices among 610 German consumers using a discrete choice experiment. Mixed logit and latent class logit models were used to model consumers' preference heterogeneity. Findings-Results show that consumers' preferences for fish attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 34 publications
1
29
1
Order By: Relevance
“…According to Laureati et al [30], the willingness to accept this kind of meat and fish was higher in males than females, and higher in students and university staff than outside the university. The ratio of preference was also higher in males and younger age groups in the study of Ankamah-Yeboah et al [42]. Verbeke et al [29] also observed that feeding animals with insects was more acceptable for men than for women; however, it was independent of age.…”
Section: Secondary School Higher Education P-valuementioning
confidence: 85%
See 1 more Smart Citation
“…According to Laureati et al [30], the willingness to accept this kind of meat and fish was higher in males than females, and higher in students and university staff than outside the university. The ratio of preference was also higher in males and younger age groups in the study of Ankamah-Yeboah et al [42]. Verbeke et al [29] also observed that feeding animals with insects was more acceptable for men than for women; however, it was independent of age.…”
Section: Secondary School Higher Education P-valuementioning
confidence: 85%
“…Another 36% answered that they would be willing to accept the fish if the price, safety, and taste remained unchanged, while 10% were unwilling to eat insect-fed fish. In a survey [42], it was found that 77% of Danish consumers were indifferent to feeding fish with an insect-containing diet, but the remaining 23% were sensitive to it. The acceptance of trout was compared according to their consumption or not of insects [43].…”
Section: Willingness To Consume Animal Products That Originated From mentioning
confidence: 99%
“…A general consensus was found among consumers, with only 10% of the sample opposed to the inclusion of insects into fish feed, and stakeholders, provided the feeds are proven to be safe, reliable, and cost effective. To the best of our knowledge, only two recent papers have focused on determinants of consumers’ acceptance of insects in animal feed via experimental procedures [56,57]. Ankamah-Yeaboah et al [56] analyzed data collected from an online questionnaire administered to 610 German consumers, using a discrete choice experiment (DCE) in order to resemble a real market decision-making setting.…”
Section: Are Consumers Ready For Insects As Feed?mentioning
confidence: 99%
“…To the best of our knowledge, only two recent papers have focused on determinants of consumers’ acceptance of insects in animal feed via experimental procedures [56,57]. Ankamah-Yeaboah et al [56] analyzed data collected from an online questionnaire administered to 610 German consumers, using a discrete choice experiment (DCE) in order to resemble a real market decision-making setting. According to their results, most consumers interviewed were not concerned about the type of feed.…”
Section: Are Consumers Ready For Insects As Feed?mentioning
confidence: 99%
“…insects as feed, all in European countries including Belgium [33], France [34], Germany [35], Poland [36], Italy [37,38] and the United Kingdom [39]. Overall, these studies found a favourable attitude and willingness to accept insects in animal feed and resulting products from animals fed with IBF among respondents.…”
Section: Introductionmentioning
confidence: 98%